Technology For Increasing Mathematical Literacy In Primary School Students - Umarova G.M. (Euro Asian Journal Publishing, 2024)
It is today's demand to make the lessons interesting and easy with new technologies for the formation of the child's mathematical literacy, cognitive activity, and interest in logical issues. It was mentioned about the method of explaining to students that mathematical knowledge is the basis for learning all knowledge.
Keywords: Junior school age; cluster technology logical problems; mathematical crosswords